2010
DOI: 10.1074/jbc.m110.155309
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Enhance Estrogen-dependent Expression of the Multidrug Transporter Gene ABCG2 through Estrogen Receptor and NFκB Cooperativity at Adjacent Response Elements

Abstract: Constitutive activation of NFB in estrogen receptor (ER)-positive breast cancer is associated with tumor recurrence and development of anti-estrogen resistance. Furthermore, a gene expression signature containing common targets for ER and NFB has been identified and found to be associated with the more aggressive luminal B intrinsic subtype of ER-positive breast tumors. Here, we describe a novel mechanism by which ER and NFB cooperate to up-regulate expression of one important gene from this signature, ABCG2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 55 publications
3
62
1
Order By: Relevance
“…However, there are relatively few examples of ER and NF-B working together to increase transcription (1,30,45,53). Recently, we found that these factors can work cooperatively on a number of genes, including PTGES, which codes for prostaglandin E synthase, and ABCG2, which codes for a drug efflux pump (17,43). For these genes, we demonstrated that NF-B may potentiate ER action by stabilizing ER occupancy on DNA at functional EREs.…”
Section: T He Estrogen Receptor (Er) Is Expressed In Approximately 75%mentioning
confidence: 99%
“…However, there are relatively few examples of ER and NF-B working together to increase transcription (1,30,45,53). Recently, we found that these factors can work cooperatively on a number of genes, including PTGES, which codes for prostaglandin E synthase, and ABCG2, which codes for a drug efflux pump (17,43). For these genes, we demonstrated that NF-B may potentiate ER action by stabilizing ER occupancy on DNA at functional EREs.…”
Section: T He Estrogen Receptor (Er) Is Expressed In Approximately 75%mentioning
confidence: 99%
“…Reasons of such contradicting data are not known, but may be related to cell-or organspecific regulation (e.g., organ-specific promoters) or whether transcriptional or posttranscriptional regulation plays a predominant role in experimental systems used in these studies or if there are cooperative interactions between hormones and other regulatory factors. Binding of ER has been shown to enhance transcriptional regulation of the ABCG2 gene by cytokines through p65 or NFkB (189).…”
Section: Regulation Of Bcrp Expressionmentioning
confidence: 99%
“…More specific support for a mechanism of inflammation-mediated modulation of ESR1 comes from more recent discoveries implicating inflammatory and leukocyte-derived cytokines (West et al 2012) and factors (Stossi et al 2012a, Vlaicu et al 2013 as extracellular agents that suppress ESR1 (discussed below). Multiple inflammatory cytokines have been implicated in suppression of ESR1 in breast cancer (Table 1) level of particular ER-target gene promoters (Rubio et al 2006, Pradhan et al 2010. Similarly conflicting findings have been reported for IL6, which was shown to induce methylation of the ESR1 promoter in vitro resulting in reduced levels of ER and an increase in basal-like gene expression patterns (D'Anello et al 2010).…”
Section: Mechanisms Of Inflammation-mediated Er Suppressionmentioning
confidence: 87%